Infections Caused by Antimicrobial Drug-Resistant Saprophytic Gram-Negative Bacteria in the Environment - Raphael, Eva; Riley, Lee W. (Frontiers in Medicine, 2017)
Background: Drug-resistance genes found in human bacterial pathogens are increasingly recognized in saprophytic Gram-negative bacteria (GNB) from environmental sources. The clinical implication of such environmental GNB is unknown. Objectives: We conducted a systematic review to determine how often such saprophytic GNBs cause human infections. Methods: We queried PubMed for articles published in English, Spanish, and French between January 2006 and July 2014 for 20 common environmental saprophytic GNB species, using search terms “infections”, “human infections”, “hospital infection”. We analyzed 251 of 1275 non-duplicate publications that satisfied our selection criteria. Saprophytes implicated in blood stream infection (BSI), urinary tract infection (UTI), skin and soft tissue infection (SSTI), post-surgical infection (PSI), osteomyelitis, and pneumonia were quantitatively assessed. Results: Thirteen of the 20 queried GNB saprophytic species were implicated in 674 distinct infection episodes from 45 countries. The most common species included Enterobacter aerogenes, Pantoea agglomerans, and Pseudomonas putida. Of these infections, 443 (66%) had BSI, 48 (7%) had SSTI, 36 (5%) had UTI, 28 (4%) had PSI, 21 (3%) had pneumonia, 16 (3%) had osteomyelitis, and 82 (12%) had other infections. Nearly all infections occurred in subjects with co-morbidities. Resistant strains harbored extended-spectrum beta-lactamase (ESBL), carbapenemase, and metallo-β-lactamase genes recognized in human pathogens. Conclusions: These observations show that saprophytic GNB organisms that harbor recognized drug-resistance genes cause a wide spectrum of infections, especially as opportunistic pathogens. Such GNB saprophytes may become increasingly more common in healthcare settings, as has already been observed with other environmental GNBs such as Acinetobacter baumanii and Pseudomonas aeruginosa.